Converting in Secret: Legal Issues among Muslim Converts in Malaysia: (Kerahsiaan Kemasukan Islam: Isu Undang-Undang Kes Pemelukan Islam Saudara Baru di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2020)
This article discusses the issue of secret conversion to Islam among muallaf (Muslim converts) in Malaysia. The objective of the research is to analyse the impact of such secrecy on court decisions in cases of conversion to Islam, which create conflict between the Shariah law and civil law. This is a qualitative study using content analysis approach with reference to primary and secondary sources. It also involves a semi-structured interview with several officers involved in this field. The data collected is analyzed through descriptive and thematic approaches. The study finds that the secret conversion to Islam by muallaf causes difficulties to judges in deciding cases, due to the conflict of laws applicable between both parties in the case. Furthermore, such secrecy is the main factor muallaf are able to avoid responsibilities they may have had previously under civil law. In contrast, for those muallaf who announced their conversion to Islam, their cases can be decided quickly according to the particular courts' jurisdictions to the satisfaction of all parties involved in the case. This research concludes making announcement of conversion to Islam mandatory is seen as the best solution in handling the conflict of jurisdiction between the civil and Shariah courts in Malaysia.Keywords: secrecy, conversion to Islam, Malaysian law, muallaf, conflict of laws